Sosialisasi dan Edukasi Pencegahan Stunting: Upaya Pengabdian Masyarakat untuk Generasi Sehat - Sarasmitha, Citra; Razak, Mochamad Rifqi Hasan Abdul; Devi, Yohana Shanta; Safitri, Ajeng Dena; Lukas, Velya Natalya Cristy (Institut Teknologi Adhi Tama Surabaya, 2024)
Stunting is a condition that adversely affects children's physical and cognitive development, affecting their health and future productivity. The socialization and education program for stunting prevention to residents of RW 03 Karangbesuki Village has succeeded in raising awareness about the importance of balanced nutrition, exclusive breastfeeding, and good sanitation to prevent stunting. The service team provided educational materials, held pre-tests and post-tests, and distributed nutritious gifts. The results of the evaluation showed a significant increase in participants' understanding of stunting. This education has succeeded in providing new knowledge to parents about the importance of their active role in maintaining children's health, as well as contributing to efforts to build more qualified human resources